(untitled) (EU and comparative law issues and challenges series (ECLIC), 2024)
Bid-rigging, a form of cartel agreement where competitors collude to manipulate the outcome of tenders, poses significant threats to fair competition and public finances. Despite intensified global and EU-level efforts to combat bid rigging, public procurement remains vulnerable to such practices, underscoring the need for ongoing research and regulatory refinement to address collusion effectively. This paper examines both public and private enforcement mechanisms targeting bid-rigging cartels in the EU, with an emphasis on sanctions - specifically the challenges of debarment mechanisms and compensation for damages arising from these practices. The paper provides an overview of bid-rigging strategies, an analysis of debarment mechanisms (specifically bidder exclusion and director disqualification), and addresses selected private enforcement issues, exploring both the potential victims of bid rigging and the barriers to obtaining compensation. Through this analysis, the paper offers insights into strengthening enforcement measures to promote fair competition and protect public resources.